Islamic Financial Literacy among Students Attending Faculty of Islamic Economics and Business - Hisan, Khairatun (IHTIYATH : Jurnal Manajemen Keuangan Syariah, 2019)
This study aims to find out Islamic financial literacy level of students enrolling in the Faculty of Islamic Economics and Business IAIN Langsa as well as factors affecting it. A sample of 236 respondents was drawn from the population using Slovin formula and the questionnaires were distributed randomly. Descriptive statistics and one-way ANOVA were used to analyse the collected data. The results indicate that Islamic financial literacy level is 65.9% categorised as medium and among the factors affecting it is the age of respondent (p value 0.036 < α 0,05).